Using Six-Sigma to measure the quality performance of the Department of Statistics-University of Baghdad-Case Study - حمود, مناف يوسف; نبيل, قتيبة; فدعم, انتصار عريبي (Journal of Economics and Administrative Sciences, 2013)
Abstract             This research was to provide a definition of quality, dimensions and concepts, whether traditional or modern concept, as well as review the dimensions of quality in higher education and vision and mission with the overall objectives of the Statistics Department.         After reviewing quality goals and purposes achieved as well as the mechanisms used to achieve them. and use standard Six-Sigma as one of the methodologies used in quality with the historical roots of using this methodology and methods applied and their definitions to the DMAIC model statement together with the formulae for finding the Six-Sigma level. Through the application which based on the data of the number of students in Department of Statistics-Baghdad University for the academic year 2010-2011, the result showed that the department of statistics lied at the second level of six –sigma.